Youth between violence and the pursuit of peace - Solarte Castro, Lina (Sociedad y Economía, 2010)
Making a retrospective study, with four sets of young people with similar socioeconomic conditions (men and women), it is intended to detect related and divergent characteristics in their reconstructed life trajectories. This will allow to approach near to a better understanding of the social logic and motivation that makes these young people take different ways between the violence and the healthy coexistence.